2017
DOI: 10.1039/c6ob02431a
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of new fluorinated liquid crystals bearing a CF2CF2 fragment with negative dielectric anisotropy

Abstract: We designed unique negative dielectric molecules, which were tricyclic compounds with a 5,5,6,6-tetrafluorocyclohexa-1,3-diene moiety in the mesogen, and then for the first time developed an effective synthetic protocol from commercially available 4-bromo-3,3,4,4-tetrafluorobut-1-ene. We also evaluated their physical properties for new mesogenic compounds, such as birefringence, dielectric anisotropy and shear viscosity, which are important characteristics for flat LC display device applications. The molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Finally, with compound 4a in hand, the successive hydrogenation in the presence of 20 mol % of Pd/C in methanol was performed for 1 d and generated the corresponding tetrafluorinated cyclohexane-1,4-diol 3a in quantitative yield. Compound 3a could be converted to the cyclohexadiene 1a in 82% isolated yield under the influence of a large amount of phosphorus oxychloride in pyridine at 90 °C for 1 d according to the previous literature [ 12 ]. On the other hand, 4a could also be transformed into the corresponding bisxanthate derivative 9a according to the literature procedure [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with compound 4a in hand, the successive hydrogenation in the presence of 20 mol % of Pd/C in methanol was performed for 1 d and generated the corresponding tetrafluorinated cyclohexane-1,4-diol 3a in quantitative yield. Compound 3a could be converted to the cyclohexadiene 1a in 82% isolated yield under the influence of a large amount of phosphorus oxychloride in pyridine at 90 °C for 1 d according to the previous literature [ 12 ]. On the other hand, 4a could also be transformed into the corresponding bisxanthate derivative 9a according to the literature procedure [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, as shown in Fig. 1 , tricyclic molecules containing a CF 2 CF 2 carbocycle, e.g., the 5,5,6,6-tetrafluorocyclohexa-1,3-diene [ 12 ] or the 1,1,2,2-tetrafluorocyclohexane motif [ 13 ], were successfully synthesized and found to exhibit a large negative Δε value (−7.3 for 1c and −9.4 for trans - 2c ) [ 14 ]. This indicated that these compounds are promising candidates for vertical alignment (VA)-type display materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the group of Konno exploited their strategy of lithiating bromide 73 in the preparation of a new class of liquid‐crystalline compounds – tricyclic 1,4‐disubstituted 5,5,6,6‐tetrafluorocyclohexa‐1,3‐dienes (e.g. 155 – 157 , Scheme ) . Moreover, the authors also include a detailed evaluation of the compounds' physical properties, most of which make the products highly attractive candidates for modern high‐performance displays, although their usefulness is still hampered by large shear viscosity.…”
Section: Applications Of Cf2cf2‐containing Compoundsmentioning
confidence: 99%
“…In addition to the development of a convenient access to CF 2 CF 2 -containing pyranoses [ 12 ], our group also showed that tricyclic mesogens with a CF 2 CF 2 -containing carbocycle exhibited large negative dielectric anisotropies ( Fig. 1 ), which would be promising for candidates for vertically aligned (VA)-type display materials [ 13 17 ]. Owing to such valuable applications, the development of a much more efficient synthetic protocol for CF 2 CF 2 -containing organic molecules has a high priority in various research areas.…”
Section: Introductionmentioning
confidence: 99%